2021
DOI: 10.1042/bcj20200835
|View full text |Cite|
|
Sign up to set email alerts
|

Cutin:cutin-acid endo-transacylase (CCT), a cuticle-remodelling enzyme activity in the plant epidermis

Abstract: Cutin is a polyester matrix mainly composed of hydroxy-fatty acids that occurs in the cuticles of shoots and root-caps. The cuticle, of which cutin is a major component, protects the plant from biotic and abiotic stresses, and cutin has been postulated to constrain organ expansion. We propose that, to allow cutin restructuring, ester bonds in this net-like polymer can be transiently cleaved and then re-formed (transacylation). Here, using pea epicotyl epidermis as the main model, we first detected a cutin:cuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 94 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…In addition, temporal analysis showed that genes with different expression trends between the graft and original wax gourds were significantly enriched in cutin, suberin, and wax biosynthesis ( Figures 5 , 6 ). Cutin is a major component of cuticle, which could protect the plant from biotic and abiotic stresses ( Xin et al., 2021 ). Cutin and suberin are hydrophobic lipid biopolyester components of the cell walls of specialized plant tissue and cell-types, where they facilitate adaptation to terrestrial habitats ( Philippe et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, temporal analysis showed that genes with different expression trends between the graft and original wax gourds were significantly enriched in cutin, suberin, and wax biosynthesis ( Figures 5 , 6 ). Cutin is a major component of cuticle, which could protect the plant from biotic and abiotic stresses ( Xin et al., 2021 ). Cutin and suberin are hydrophobic lipid biopolyester components of the cell walls of specialized plant tissue and cell-types, where they facilitate adaptation to terrestrial habitats ( Philippe et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profiling can be further combined with various multi-omics technologies, typically metabolome ( Fernandez-Moreno et al, 2016 ) and proteome ( Szymanski et al, 2017 ), and with large scale sequencing of genetic diversity ( Szymański et al, 2020 ) to assign putative functions to the genes and explore their role in cuticle formation. Novel functions revealed by biochemical approaches, e.g., the cutin:cutin-acid endo-transacylase (CCT) enzyme activity ( Xin et al, 2021 ), may also ultimately lead to the isolation of the encoding gene.…”
Section: Exploring the Function Of Cuticle-associated Genes Through Reverse Genetics Approaches In Tomatomentioning
confidence: 99%